Syncytiotrophoblast stress in preeclampsia: the convergence point for multiple pathways - Redman, Christopher W.G.; Staff, Anne Cathrine; Roberts, James M. (American journal of obstetrics and gynecology, 2022)
Preeclampsia evolves in 2 stages: a placental problem that generates signals to the mother to cause a range of responses that comprise the second stage (preeclampsia syndrome). The first stage of early-onset preeclampsia is poor placentation, which we here call malplacentation. The spiral arteries are incompletely remodeled, leading to later placental malperfusion, relatively early in the second half of pregnancy. The long duration of the first stage (several months) is unsurprisingly associated with fetal growth restriction. The first stage of late-onset preeclampsia, approximately 80% of total cases, is shorter (several weeks) and part of a process that is common to all pregnancies. Placental function declines as it outgrows uterine capacity, with increasing chorionic villous packing, compression of the intervillous space, and fetal hypoxia, and causes late-onset clinical presentations such as “unexplained” stillbirths, late-onset fetal growth restriction, or preeclampsia. The second stages of early- and late-onset preeclampsia share syncytiotrophoblast stress as the most relevant feature that causes the maternal syndrome. Syncytiotrophoblast stress signals in the maternal circulation are probably the most specific biomarkers for preeclampsia. In addition, soluble fms-like tyrosine kinase-1 (mainly produced by syncytiotrophoblast) is the best-known biomarker and is routinely used in clinical practice in many locations. How the stress signals change over time in normal pregnancies indicates that syncytiotrophoblast stress begins on average at 30 to 32 weeks’ gestation and progresses to term. At term, syncytiotrophoblast shows increasing markers of stress, including apoptosis, pyroptosis, autophagy, syncytial knots, and necrosis. We label this phenotype the “twilight placenta” and argue that it accounts for the clinical problems of postmature pregnancies. Senescence as a stress response differs in multinuclear syncytiotrophoblast from that of mononuclear cells. Syncytiotrophoblast irreversibly acquires part of the senescence phenotype (cell cycle arrest) when it is formed by cell fusion. The 2 pathways converge on the common pathologic endpoint, syncytiotrophoblast stress, and contribute to preeclampsia subtypes. We highlight that the well-known heterogeneity of the preeclampsia syndrome arises from different pathways to this common endpoint, influenced by maternal genetics, epigenetics, lifestyle, and environmental factors with different fetal and maternal responses to the ensuing insults. This complexity mandates a reassessment of our approach to predicting and preventing preeclampsia, and we summarize research priorities to maximize what we can learn about these important issues.